Resilience, optimism and social support among international students - Sabouripour, Fatemeh; Roslan, Samsilah (Canadian Center of Science and Education, 2015)
This study focuses on the examination of the relationship between resilience, optimism and social support among international students. International students who are studying as foreign students tend to experience greater stress and anxiety during their study. They need to adjust to the new environment and overcome challenges. The resilience level of students is very important as it can help them adjust their life pressures and stresses. The current study aims to look at the levels and patterns of resilience, optimism and social support among international students. The instruments used were Connor-Davidson Resilience Scale (CD-RISC) for resilience, Life Orientation Test Revised (LOT-R) for optimism and Multidimensional Scale of Perceived Social Support (MSPSS) for social support. A total of 291 international students were involved in the study. The findings revealed a significant difference in the resiliency level across races, with African students scoring higher than others. The regression analysis employed showed that optimism (B=. 593) and social support (B=. 204) are significant predictors of resilience.